Effectiviness Of Leaflet As The Health Promotion Medium About Breast Milk - Rusnawati; Mitra Asriani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2018)
The development of health promotion media in disease prevention management has been carried out. This study aims to determine whether the leaflet medium influences the mother's knowledge about exclusive breastfeeding. This study used a quasi-experimental design with a pre-test and post-test group design. Using 50 samples selected by purposive sampling. Based on the results of the Wilcoxon signed-rank test statistical test the average respondent's knowledge for Exclusive Asi and IMD before the intervention was given with a leaflet was 3.90 while after being given the intervention it increased by 2.84 points to reach 6, 74 in the post-test results with a P value of 0,000 where <0.05. For knowledge about ASI, the pretest results obtained were 5.86 and 9.60 posttest results. This shows that after the intervention of respondents' knowledge about breastfeeding increased by 3.47 points with a P-value of 0,000 which is more than 0.05. The conclusion that can be drawn from this study is that a very effective leaflet is used as a health promotion medium for breastfeeding.